Experiences, impacts, and requirements of synchronous video consultations between nurses, allied health professionals, psychological therapists, and adult service-users: A review of the literature. - Lynn Mcvey; Martin Fitzgerald; Jane Montague; Claire Sutton; Peter Branney; Amanda Briggs; Michael Chater; Lisa Edwards; Emma Eyers; Karen Khan; Zaid Olayiwola Olanrewaju; Rebecca Randell (PLOS Digital Health)
Background Telemedicine is increasingly used within healthcare worldwide. More is known about its efficacy in treating different conditions and its application to different contexts than about service-users' and practitioners' experiences or how best to support implementation. Aims To review adult service-users' experiences of synchronous video consultations with nurses, allied health professionals and psychological therapists, find out how consultations impact different groups of service-users and identify requirements for their conduct at individual, organisational, regional, and national levels. Method CINAHL, Embase, Medline, PsycINFO Scopus were searched for papers published between 01/01/2018 and 19/03/2021. One reviewer independently reviewed citations and a second reviewed those excluded by the first, in a liberal accelerated approach. Quality assessment was undertaken using the Mixed Methods Appraisal Tool and data were synthesised narratively. Results 65 papers were included. Service-users' experiences of video consultations ranged from feelings of connection to disconnection and ease of access to challenges to access. Many were excluded from video consultation services or research, for example because of lack of access to technology. Individual service-users required clear orientation and ongoing technical support, whereas staff needed support to develop technical and online-relational skills. At organisational levels, technology needed to be made available to users through equipment loan or service models such as hub-and-spoke; services required careful planning and integration within organisational systems; and security needed to be assured. Regional and national requirements related to interorganisational cooperation and developing functionality. Conclusion To support safe and equitable video consultation provision, we recommend: (1) providers and researchers consider how to maximise participation, for example through inclusive consent processes and eligibility criteria; (2) sharing video consultation user guides and technical support documentation; and (3) continuing professional development for practitioners, focusing on the technical and relational skills that service-users value, such as the ability to convey empathy online.